Risk factors for hearing loss in elderly - doi: 10.5020/18061230.2012.p176 - Martins, Kelly Vasconcelos Chaves (2012)
Objective: To identify risk factors related to sensorineural hearing loss in elderly. Methods: The sample consisted of 60 selected elderly, divided into two groups: the Case Group, composed by 30 individuals, 21 females and 9 males, aged at least 60 years, presenting sensorineural hearing loss, and the Control Group, composed by 30 individuals matched on gender and age, with normal hearing. The patients were submitted to audiological anamnesis and tonal audiometry. The hearing impairment was defined according to average threshold greater than 35dBNA, in the frequencies of 1,000; 2,000 and 4,000 Hz, in the best ear. Results: Statistically significant odds ratios were: a) to audiological history: noise exposure and family history of deafness; b) to situations involving hearing difficulty: television, church, telephone, silent environment, spatial location of sound, difficulty with voices and noisy environment; c) to otologic history: tinnitus, otorrhea and nausea; and d) to medical history: visual problems, smoke, alcohol, thyroid problems and kidney disease. Conclusion: The findings of this study highlighted, for sensorineural hearing loss, risk factors related to audiologic, otologic and medical history, and to situations involving hearing difficulty